AN EFFECT OF SOCIODRAMA METHOD IMPLEMENTATION IN STUDENTS LANGUAGE SKILL AT FOURTH GRADE ELEMENTARY SCHOOL IN CLUSTER XII OF BULELENG DISTRICT - Tristiantari, Ni Ketut Desia (Journal of Education Technology, 2017)
This study aimed at finding the effect of sociodrama method influence upon students’ skills of listening, speaking, reading, and writing. This study is a quasi-experiment which the data were analysed by using MANOVA. The samples were 75 students class IV of Public Elementary Schools in Cluster XII of Buleleng District. 37 students became the subject of experiment class and 38 students became the subjects in control class. The four data were collected by using language skill evaluation in form of written and performance test. The finding shows that: (1) There was a difference of listening skill between the students who followed the sociodrama method with students who followed conventional teaching method; (2) There was a difference of reading skill between the students who followed the sociodrama method with students who followed conventional teaching method; (3) There was a difference of writing skill between the students who followed the sociodrama method with students who followed conventional teaching method; (4) There was a difference of speaking skill between the students who followed the sociodrama method with students who followed conventional teaching method; (5) Simultaneously there was a difference of listening, reading, writing and speaking skills of the students who followed the sociodrama method with students who followed conventional teaching method.